Los roles de enfermería y su influencia en la calidad de atención a pacientes del hospital Martín Icaza Del Cantón Babahoyo. Los Ríos. Primer semestre 2018 - Romero Ricaurte, Edinson Fernando (2018)
Having as problematic the different dissatisfactions or inconveniences exhibited by users or relatives in different communication media regarding the quality of care received in health institutions, this study focuses on determining the influence of nursing roles on the quality of care provided. patients from the Martín Icaza Hospital of the Babahoyo canton. The rivers. First semester 2018. In the development of this research work, the inductive method and the qualitative-quantitative modality are applied. Framing the types of research: basic, bibliographic or documentary, descriptive and transversal. The technique of data collection to be used is the interview, applying questionnaires of questions to patients and nursing professionals from the internal medicine areas of the Martin Icaza Hospital. After the analysis of the information collected, we can establish that the roles of nursing, specifically the care role directly influences the quality of care perceived by patients, who 74.7% said that sometimes it is the professional nurses who provide the care, of which only 5.7% qualifies nursing care as good and 69.0% as regular. It was also possible to detect that the number of nursing professionals is not adequate for the demand of patients in the areas. Concluding that the quality of nursing care is influenced by the shortage of professional nurses, limiting the execution of their roles specifically the assistance reflected in the patient's perception.